Planiglobii Terrestris Mappa Universalis: Utrumq Hemisphærium Orient. et Occidentale Repræsentans ex IV Mappis Generalibus Mappe-monde qui Represente les Deux Hemispheres Savoir Celui de l'Orient et Celui de l'Occident Tirée des Quatre Cartes Generales - Hase, Johann Matthias (Homann Heritiers, 1746)
This world map from the German mathematician, historian, and geographer Johann Matthias Hase shows the major cities, islands, and the major political divisions between the two hemispheres. Hase includes six auxiliary maps, four of which show the globe from different perspectives (such as the north and south pole) and two which show the tilt of the earth during the summer and winter solstice. In the right and left corners sit two title cartouches, the left in Latin and the right in French. The Latin cartouche is decorated with illustrations of mythical sea creatures (such as a hippocamp), coral, a man holding some coral while blowing a horn, and personifications of the winds. More realistic and land based animals surround the French cartouche, such as a deer, dog and parrot. Four crowns, probably representing the four corners of the world, sit on platforms around this cartouche as well.